Evaluation of Authentic Assessment Implementation in SDN 101775 Sampali, Deli Serdang Regency, Academic Year 2019/2020 - Syarifah Aini; Deny Setiawan; Siman Siman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research is an evaluation research with a quantitative descriptive approach. The evaluation model used is the Stake Countenance Model. The subjects of this study were all teachers in SDN 101775 Sampali, Deli Serdang Regency with a total of 12 teachers. Data collection techniques using observation, questionnaires, documentation and interviews. In analyzing data using descriptive methods. From the results of research conducted on the evaluation of the implementation of authentic assessment in SDN 101775 Sampali Deli Serdang Regency with a stake countenance evaluation model that is 90.39%. This is evidenced from the three stages of stakeholder evaluation in the implementation of authentic assessment which consists of an input phase (antecendents phase) which is evaluated consisting of analysis of learning documents, attitude assessment documents, knowledge assessment documents and skills assessment very well complete with a percentage of 89.46% . In the transaction phase that was evaluated, namely how the authentic assessment carried out by the teachers at SDN 101775 Sampali was carried out very well with a percentage of 90.71%. In the evaluated outcome phase which is the reporting of student learning outcomes and teacher understanding of the implementation of authentic assessment in schools has been going very well with a percentage of 91%. The next suggestion for the implementation of authentic assessment is continuously monitored so that the teacher's understanding of the implementation of authentic assessment can be carried out properly.